Reproducible and scalable purification of extracellular vesicles using combined bind-elute and size exclusion chromatography - Corso, G; Mäger, I; Lee, Y; Görgens, A; Bultema, J; Giebel, B; Wood, M; Nordin, J; Andaloussi, S (Springer Nature, 2017)
Extracellular vesicles (EVs) play a pivotal role in cell-to-cell communication and have been shown to take part in several physiological and pathological processes. EVs have traditionally been purified by ultracentrifugation (UC), however UC has limitations, including resulting in, operator-dependant yields, EV aggregation and altered EV morphology, and moreover is time consuming. Here we show that commercially available bind-elute size exclusion chromatography (BE-SEC) columns purify EVs with high yield (recovery ~ 80%) in a time-efficient manner compared to current methodologies. This technique is reproducible and scalable, and surface marker analysis by bead-based flow cytometry revealed highly similar expression signatures compared with UC-purified samples. Furthermore, uptake of eGFP labelled EVs in recipient cells was comparable between BE-SEC and UC samples. Hence, the BE-SEC based EV purification method represents an important methodological advance likely to facilitate robust and reproducible studies of EV biology and therapeutic application.